Sistemas de telediagnóstico: Maletín médico de ingeniería aplicada - Villalpando, Manuel; Velázquez Guerrero, Ramiro; Gutiérrez Mier, Pedro Angel (Revista Mexicana de Ingenieria Biomedica, 2001)
Nowadays the advancement of technology permits the development of software solutions applied to medicine that facilitates reaching an increasing number of persons indistinctly of their geographic position in order to attend to their health problems. This paper is devoted to the development of a medical briefcase conceived to be used as a telemedicine system. This equipment is a set of medical instrumentation modules that use the computer as a tool, offering not only the basic characteristics of traditional medical instrumentation but also the capability of analysis and remote transmission of physiological information in order to perform telediagnosis tasks. One of its main advantages is that it offers high-quality results in cardiology diagnosis and telediagnosis at low cost. General hardware and software design aspects are described. In conclusion, the system’s performance and the results obtained are presented and discussed.